Risk factors for a post-operative neutrally aligned total knee arthroplasty in the sagittal plane developing fixed flexion deformity at 2 years follow up study - Silva, Amila; Tan, Sharon; Tay, Adriel; Nee Pang, Hee; Nung Lo, Ngai; Jin Yeo, Seng (International Journal of Research in Orthopaedics, 2019)
Background: The incidence of fixed flexion deformity (FFD) following total knee arthroplasty (TKA) has been reported to be as high as 17%, increasing demand on the quadriceps and hindering mobility. The aim of this study is then to identify these predictors for the development of FFD. Methods: In this retrospective study, all patients who underwent primary TKA from January 2008 to June 2009 at a single institution were identified. All patients with neutral alignment in the sagittal place of the knee intra-operatively were identified and followed up. The knee motion was measured in both operated and contralateral knees and followed-up for a minimum of 24 months post-operatively. Results: Multivariate analysis demonstrated pre-operative FFD of the non-operated knee (p-value 0.03), pre-operative range of motion of the operated knee (p-value 0.01) and non-operated (p-value 0.01) knee and pre-operative maximum flexion of the operated knee (p-value 0.001) to be independent risk factors for development of FFD at 24 months. Conclusions: Independent risk factors for the development of post-operative FFD in TKA are pre-operative FFD of the operated knee, FFD of the non-operated knee and the maximum flexion of the operated knee. The relative risk of a male developing FFD is also as high as 1.34.